1999
DOI: 10.1046/j.1464-410x.1999.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of nephrostomy, JJ stent and urgent in situ extracorporeal shock wave lithotripsy for obstructing ureteric stones

Abstract: Objectives To determine the optimal method of treatpreference or the availability of urgent ESWL. The success rate was measured by the disintegration of ment for ureteric stones causing complete obstruction, treated by insertion of a JJ stent or a nephrostomy the stone and spontaneous passage after ESWL; failure was defined as the need for additional procedure(s) for tube, followed by extracorporeal shock wave lithotripsy (ESWL) or by urgent in situ ESWL if readily stone extraction. Results Urgent in situ ESWL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…21 In our experience, we obtained a reasonable initial stone-free rate and an encouraging stone-free rate at 1 month. Thus, our patients had their problem solved in a relatively short period and with no need of additional bothersome auxiliary procedures, such as has been reported from other series in those undergoing emergency ESWL 5,6,10,22 (Table 2).…”
Section: Commentsupporting
confidence: 52%
See 3 more Smart Citations
“…21 In our experience, we obtained a reasonable initial stone-free rate and an encouraging stone-free rate at 1 month. Thus, our patients had their problem solved in a relatively short period and with no need of additional bothersome auxiliary procedures, such as has been reported from other series in those undergoing emergency ESWL 5,6,10,22 (Table 2).…”
Section: Commentsupporting
confidence: 52%
“…Nevertheless, its potential disadvantages include leakage, dislodgement of the tube, and the need to manage the stoma. 10 Insertion of a double-J stent, apart from complications such as ureteral perforation and failure to pass the stent in some cases, may increase the risk of urosepsis. Furthermore, the presence of a stent results in a reduction of the shock wave energy reaching the stone and causes ureteral constriction and edema of the wall, both of which may reduce the chance of successful fragmentation or the passage of fragments after ESWL.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used ESWL within 14 days of the onset of acute renal colic but under anesthesia (10) or even during acute renal colic (7) or acute renal failure (11). Moreover, a comparative retrospective analysis has shown that, in emergency situations, ESWL is more effective than nephrostomy or a double J stent and has very low morbidity (12).…”
Section: Introductionmentioning
confidence: 99%